Um estudo numérico sobre a utilização de telas visando a fixação de dunas e proteção do solo - Lima, Izael Araújo (2018)
Sand fences are widely applied to prevent soil erosion by wind in areas affected by desertification. Sand fences also provide a way to reduce the emission rate of dust particles, which is triggered mainly by the impacts of wind-blown sand grains onto the soil and affects the Earth’s climate. Many different types of fence have been designed and their effects on the sediment transport dynamics studied since many years. However, the search for the optimal array of fences has remained largely an empirical task. In order to achieve maximal soil protection using the minimal amount of fence material, a quantitative understanding of the flow profile over the relief encompassing the area to be protected including all employed fences is required. Here we use Computational Fluid Dynamics to calculate the average turbulent airflow through an array of fences as a function of the porosity, spacing and height of the fences. Specifically, we investigate the factors controlling the fraction of soil area over which the basal average wind shear velocity drops below the threshold for sand transport when the fences are applied. We introduce a cost function, given by the amount of material necessary to construct the fences. We find that, for typical sand-moving wind velocities, the optimal fence height (which minimizes this cost function) is around 50 cm, while using fences of height around 1.25 m leads to maximal cost. We find that the area of soil protected against direct aerodynamic entrainment has two regimes, depending on the spacing Lx between the fences. When Lx is smaller than a critical value Lxc , the wake zones associated with each fence are inter-connected (regime A), while these wake zones appear separated from each other (regime B) when Lx exceeds this critical value of spacing. The system undergoes a second order phase transition at Lx = Lxc , with the cross-wind width of the protected zone scaling with [1 − Lx /Lxc ]^β in regime A, with β ≈ 0.32.